Foreign Experience Of State Support For The Development Of Small And Medium Businesses - Imomnazar Egamberdievich Tursunov; Madinabonu Zafarzhon kizi Khasanova (Genius Journals, 2026)
International experience in state support for SMEs includes financial, tax, regulatory, and infrastructure measures, using a program-targeted approach and combining direct and indirect instruments, with the active participation of regional authorities. One of the priorities of the economic theory of the reform currently being carried out in Uzbekistan is the creation and development of small and medium-sized businesses. The development of small and medium-sized enterprises (SMEs) is characterized by its key role in the economy, including a significant contribution to GDP, exports and industry. The article highlights the role, essence and importance of the innovative economy in increasing the competitiveness of entrepreneurship, small and medium-sized businesses. The article presents foreign experiences of SME development in the context of new challenges and the formation of a national economy
Keywords: state support; innovative economy; informatization; computer technology